Molecular phylogeny of the spiny‐surfaced species of the dinoflagellate Prorocentrum with the description of P. thermophilum sp. nov. and P. criophilum sp. nov. (Prorocentrales, Dinophyceae). Issue 1 (2nd January 2023) - Gómez, Fernando; Gourvil, Priscillia; Li, Tangcheng; Huang, Yulin; Zhang, Huan; Courcot, Lucie; Artigas, Luis F.; Soler Onís, Emilio; Gutiérrez‐Rodríguez, Andrés; Lin, Senjie
Abstract : Spiny‐surfaced species of Prorocentrum form harmful algal blooms, and its taxonomic identity is obscure due to the size and shape variability. Molecular phylogenies reveal two major clades: one for P. cordatum with sequences mainly retrieved as P. minimum, and the other for P. shikokuense with sequences also retrieved as P. dentatum and P. donghaiense . Several closely related clades still need to be characterized. Here, we provide nuclear SSU and LSU rRNA genes, and nuclear ITS region (ITS1‐5.8S gene‐ITS2) sequences of the strain CCMP3122 isolated from Florida (initially named P. donghaiense ) and strains Prorocentrum sp. RCC6871–2 from the Ross Sea, Antarctica. We describe Prorocentrum thermophilum sp. nov. based on the strain CCMP3122, a species also distributed in the open waters of the Gulf of Mexico, New Zealand, and the Arabian Gulf; and Prorocentrum criophilum sp. nov. based on the strain RCC6872, which is distributed in the Antarctic Ocean and Arctic Sea. Prorocentrum thermophilum is roundish ( 14 μm long, 12 μm wide), with an inconspicuous anterior spine‐like prolongation under light microscopy, valves with tiny, short knobs (5–7 per μm 2 ), and several (<7) large trichocyst pores ( 0.3 μm) in the right valve, as well as smaller pores ( 0.15 μm). Prorocentrum criophilum is round in valve view ( 11 μm long, 10 μm wide) and asymmetrically roundish in lateral view, the periflagellar area was not discernible under light microscopy, valves with very tiny, short knobs (6–10 per μm 2 ), and at least 12 large pores in the right valve. Other potentially undescribed species of spiny‐surfaced Prorocentrum are discussed.